Can trajectories of glycemic control be predicted by depression, anxiety, or diabetes-related distress in a prospective cohort of adults with newly diagnosed type 1 diabetes? Results of a five-year follow-up from the German multicenter diabetes cohort study (GMDC-Study). (July 2018) - Kampling, Hanna; Mittag, Oskar; Herpertz, Stephan; Baumeister, Harald; Kulzer, Bernd; Petrak, Frank
Highlights: More than half of the patients show poor glycemic control during the first 5 years. We identified 4 trajectories of glycemic control based on individual HbA1c changes. Three of these trajectories included patients with poor glycemic control. Even the good control trajectory showed a steadily increasing HbA1c . 15–20% of the patients had moderate/severe depression symptoms at each measurement. Depression, anxiety, & diabetes-related distress were unrelated to glycemic control. Abstract: Aims: The longitudinal association between glycemic control with depression, anxiety or diabetes-related distress in type 1 diabetes is poorly understood. Therefore, we examined long-term trajectories of HbA1c in a new-onset cohort of adults with type 1 diabetes, and analyzed associations with depression, anxiety, and diabetes-related distress. Methods: We included 313 newly diagnosed adults with type 1 diabetes in a prospective multicenter cohort study. Depression, anxiety, and diabetes-related distress were assessed starting with the diabetes diagnosis and at five annual surveys. HbA1c-measurements started with the one-year follow-up. HbA1c trajectories were analyzed applying Growth mixture modeling, while prediction of membership in the trajectories classes was analyzed using multiple regression, and one-way ANOVA/Chi2 to identify differences between classes. Results: Average HbA1c increased constantly: follow-up at 1-year 6.5% (48 mmol/mol), 2-years 6.9% (52 mmol/mol), 3-years 7.1% (54 mmol/mol), 4-years 7.1% (54 mmol/mol), and 5-years 7.4% (57 mmol/mol). HbA1c trajectories included one 'good control' and three 'poor control' (52% of patients) classes. At the five-year follow-up, mean HbA1c was 6.3% (45 mmol/mol) in the 'good control' class, and ranging from 7.9% (63 mmol/mol) to 9.0% (75 mmol/mol) in the three 'poor control' classes. Classes were neither predicable, nor differentiated by depression, anxiety, or diabetes-related distress. Conclusions: We identified distinct trajectories of glycemic control. Depression and anxiety were highly prevalent but they neither predicted 'poor'/'good' glycemic control trajectories nor were they associated with glycemic control at any assessment point.